极区海域海冰内部有机物质研究进展 - 蔡明红; 何剑锋; 郑淑娴 (2006)
本文对极区海域海冰内部有机物质的国内外研究现状进行了扼要阐述。内容涉及海冰内部溶解态有机物质(DOM)和颗粒态有机物质(POM)的产生、迁移和转化过程;海冰内部冰藻生化组分(糖类、脂类和胞外分泌物);海冰内部有机物质在调节初级生产力和异养生物活性之间的机理研究等,并提出了今后需要重点解决的科学问题。 ea ice is a unique habitat for organisms in polar seas.The composition,distribution and abundance of organisms in sea ice vary on temporal and spatial scales and are controlled by physico-chemical and biological factors in the surrounding environment.This thesis presents an introduction of the significant study on dissolved organic matter(DOM) pools and particle organic matter(POM) in seaice systems.This thesis concludes the study on the main biological assemblages and their roles in sea ice,the mechanism of DOM and POM in the process of origin,transport and translation.The biochemical composition in the organic matter of sea ice(carbohydrate,lipids,EPS) is also discussed.It as well puts forward some scientific questions which are needed for further research. 国家自然科学基金(40576002,40006010);; 国家海洋局海洋青年科学基金(2003112)资助